Optimal zoning in the unconstrained Hotelling game1. (18th July 2014) - Bárcena‐Ruiz, Juan Carlos; Casado‐Izaga, F. Javier; Hamoudi, Hamid; Rodriguez, Isabel
Abstract: This paper studies a zoning mechanism that gives the optimal locations of two firms in a linear city under mill prices. A regulator biased towards consumers allows a central area of the city to be shared by firms and consumers and thus firms are not allowed to locate outside the city limits. A regulator more concerned about firms extends this central zone outside the city limits and the city has a residential use only if the firms so decide. Finally, a regulator highly biased towards firms allows them to locate only beyond a set distance from the city, so there is a strip of land outside the city but close to its boundaries, for alternative uses.